Hermeneutik der Zukunft als Hermeneutik der technischen Zukunft - Željko Radinković (Phainomena)
Hermeneutics of the Future as Hermeneutics of the technological Future - The text discusses the challenges that philosophy of technology increasingly faces due to the emergence of new, the so-called transclassical techniques. This applies particularly to the field of technology assessment, where a “hermeneutic turn” is emerging, within which communicative practices and strategies for understanding how to deal with new technologies are being developed, rather than consequentialist, prognostic, and scenario-based approaches. Furthermore, the contribution first highlights the diversity of hermeneutic approaches and then discusses the guiding concept of a “hermeneutics of the future” in the philosophy of technology as the constitutive primacy of the future in the existential sense.